Functional role of sepiapterin reductase in the biosynthesis of tetrahydropteridines in Dictyostelium discoideum Ax2 - Choi, Yong Kee; Kong, Jin Sun; Park, Young Shik (Biochimica et biophysica acta, 2006)
In Dictyostelium discoideum Ax2 l- erythro-tetrahydrobiopterin (BH4) is produced in much smaller amount than its stereoisomer d-threo-tetrahydrobiopterin (DH4), both of which are catalyzed by sepiapterin reductase (SR) at the terminal steps. In order to investigate their putative function and biosynthetic regulation, we performed quantitative analysis of not only the intracellular pteridines by HPLC but also the biosynthetic enzymes (GTP cyclohydrolase I, 6-pyruvoyltetrahydropterin synthase, SR, and aldose reductase-like enzyme) by Northern blot analysis and activity assay. We found that both SR transcript and activity increased in parallel with a remarkable decline in aldose reductase-like enzyme activity when BH4 increased transiently in the early development. Through in vitro assay of BH4/DH4 synthesis and in vivo rescue experiment of SR knockout mutant, we demonstrated that Dictyostelium SR favors DH4 synthesis while human SR does BH4 synthesis. The results suggest that Dictyostelium SR prefers 1′-oxo-2′- d-hydroxypropyl-tetrahydropterin to 6-pyruvoyltetrahydropterin as a substrate, thereby maintaining dominant production of DH4 over BH4 in sufficient supply of AR-like enzyme, while allowing increase of BH4 when SR prevails quantitatively over aldose reductase-like enzyme. On the other hand, a transient increase of BH4 may imply that BH4 has an independent function from DH4 in Dictyostelium.